The Acoustic Material Constructed by the Fiber of Eichhornia crassipes and Banana Peel as a Sound Pollutant-reducing Solution - Regita Dimar Asyurra; Avivah Afra Amatullah; Annisa Zaskia Putri; Mayshilla Anatayya Putri Zevly; Angga Puja Asiandu; Widya Sari (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
This study aims to evaluate and compare the effect of the composition of water hyacinth (Eichhornia crassipes) with a banana peel on the absorption coefficient value as a composite material for absorbing sound waves. The cellulose within the water hyacinth and banana peel lead to reduced overload sound waves. This study used an experimental method providing banana peel crushed into powder, water hyacinth fiber, and resin (as a catalyst). All samples were prepared with dimensions of 13.5 cm × 25 cm × 0.8 cm. A frequency generator application was used as the sound source (125, 250, 500, 1000, and 2000 Hz), while a sound meter application measured sound intensity (dB). The results indicated that the outer surface of sample D had a superior absorption coefficient, measuring 0.51 at 250 Hz and 0.45 at 2000 Hz. Meanwhile, the inner surface of sample D recorded absorption coefficients of 0.46 at 250 Hz and 0.45 at 2000 Hz. Variations in absorption values were attributed to destructive interference and saturation. Sample D contained more water hyacinth (approximately 30%) than banana peel powder. This suggests that water hyacinth and banana peel powder are viable natural fiber alternatives for sound wave absorption.